2021
DOI: 10.1017/s1041610221000776
|View full text |Cite
|
Sign up to set email alerts
|

Effects of restriction of activities and social isolation on risk of dementia in the community

Abstract: Objective: Social isolation and emotional isolation, i.e. loneliness, have been associated with dementia or cognitive decline. In contrast, the relationship of restriction of physical and instrumental activities of daily living to cognitive decline and dementia has been less studied. Design: We examined multiple quality of life (QoL) indicators, including isolation and restriction of activities, utilizing two validated scales in elders without dementia to determine their associations wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Good social engagement, on the other hand, was protective against dementia (RR = 0.88, 95% CI 0.80-0.96) (Penninkilampi et al, 2018). The paper by Goldberg et al (2021) in this issue of the Journal supports this trend in the literature, with social isolation (HR=1.78, 95%CI 1.17-2.70) being associated with episodic memory and incident dementia.…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…Good social engagement, on the other hand, was protective against dementia (RR = 0.88, 95% CI 0.80-0.96) (Penninkilampi et al, 2018). The paper by Goldberg et al (2021) in this issue of the Journal supports this trend in the literature, with social isolation (HR=1.78, 95%CI 1.17-2.70) being associated with episodic memory and incident dementia.…”
mentioning
confidence: 52%
“…Reduced social ties and cognitive activity, if associated with the restriction, are independent risk factors for dementia. As the Goldberg et al study shows, memory impairment leads to restrictions which in turn worsen cognition, although they showed that the latter effect was greater than the former (Goldberg et al, 2021). While episodic memory was examined in this study, it is quite likely that other cognitive domains, in particular executive function, have a similar reciprocal relationship with restriction.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…The severe depressive symptoms including depressed mood, fatigue, helplessness restrict patients from interacting with other people result in social isolation and feeling loneliness. Both social isolation and loneliness increases the risk of dementia thus depression could increase the risk of dementia 34 , 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The body of empirical research on loneliness among older adults goes back over half a century (Munnichs, 1964), but the past decade has seen an uptick in attention in the professional and lay-press, as well as government and public policy circles (Levine, 2018; United States Senate Special Commitee on Aging, 2020). Much of the focus over the past decade has been grounded in concern about the adverse downstream biological effects of loneliness in terms of medical comorbidity, dementia, and early mortality (Frenkel-Yosef et al, 2020;Lutzman et al, 2021;Goldberg et al, 2021). Although the biological impact of loneliness is of course important, it is at least equally if not more critical to consider the adverse effects of loneliness on quality of life and mental well-being.Loneliness by definition is a form of psychological distress, i.e.…”
mentioning
confidence: 99%